REACTIONS TO MARIANA VALVERDE - Prado, Mariana Mota; Trebilcock, Michael J. (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2020)
We are grateful to Valverde for agreeing to read and comment on our book, despite it not being squarely within her area of research and interests. Her comments bring another perspective on institutions, and her piece exposes the readers to a type of analysis with different methodological assumptions from the ones we adopt in our book. Despite these differences, there are some issues raised by Valverde that resonate with pressing concerns in the field of law and development. Our reaction will revolve around these shared concerns.